THERMOCHEMICAL CONVECTION AND HELIUM CONCENTRATIONS IN MANTLE PLUMES - Samuel H.; Farnetani C.G. (My University, 2003)
Compositionally heterogeneous material may exist in the lowermost mantle [van der Hilst and Karason, Science 283 (1999) 1885-1888]. Here we use a numerical model to investigate the dynamics of (i) the subducted oceanic crust and lithosphere, (ii) a deep layer chemically denser, relatively undegassed and enriched in radiogenic elements. Tracers carry U, Th, K, and He concentrations which vary due to radioactive decay and to partial melting and degassing processes. We investigate the stability of the denser layer and find that by considering a depth dependent thermal expansion coefficient and temperature dependent viscosity, a layer with a chemical density excess of 2.4% can remain stable and poorly mixed until present-day time. The calculated helium ratios are in good agreement with 3He/4He observed at ridges and hotspots and show that the large spectrum of helium ratios of OIB can be explained by mixing between undegassed material, recycled oceanic crust and lithosphere. For MORB, the sharp spectrum of helium ratios may be due to a degassed, homogeneous and well mixed shallow mantle.
Keywords: HELIUM; MANTLE; THERMOCHEMICAL CONVECTION